Structured Group Psychotherapy for Bipolar Disorder : the Life Goals Program - Bauer, Mark S. (Springer Pub., 2003)
Annotation This updated and substantially revised edition not only incorporates the expansion of the pharmacological armamentarium available for treatment but also integrates the explosion of evidence-based data for psychosocial interventions. The authors, a psychiatrist-nurse team, have fine-tuned their two-phase treament program and present a clear and concise approach to improving illness self-management skills, as well as social and occupational functioning.